If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1.5z + 7 = 1.5z + 1 Reorder the terms: 7 + -1.5z = 1.5z + 1 Reorder the terms: 7 + -1.5z = 1 + 1.5z Solving 7 + -1.5z = 1 + 1.5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1.5z' to each side of the equation. 7 + -1.5z + -1.5z = 1 + 1.5z + -1.5z Combine like terms: -1.5z + -1.5z = -3z 7 + -3z = 1 + 1.5z + -1.5z Combine like terms: 1.5z + -1.5z = 0.0 7 + -3z = 1 + 0.0 7 + -3z = 1 Add '-7' to each side of the equation. 7 + -7 + -3z = 1 + -7 Combine like terms: 7 + -7 = 0 0 + -3z = 1 + -7 -3z = 1 + -7 Combine like terms: 1 + -7 = -6 -3z = -6 Divide each side by '-3'. z = 2 Simplifying z = 2
| 2x^2-3xy+4y^2-3=0 | | 2n-13=39 | | X+1=6x+12 | | 7y-28=-19+6y | | 3x+10=9x-12 | | 9b-8-3b+5=21 | | 5s+8-4s= | | 971-4= | | 25n^4-9=0 | | -(8w+5)+3(w-15)= | | C^2+12c+36=0 | | 7y-28=-19+6 | | 6z-8z=-2z-24 | | 5-11w=7(5-2w) | | -8x+10=-25 | | 5.25x+6.5*4y=906.25 | | 2m^2*2m^2= | | 6x^4-x^2-5=0 | | 3(4v-8)=24+4v | | 5.2x-8=110.5 | | -5(-3g-9)= | | 12-41=3(x-2)-8 | | 5x-7+8x= | | 45x^4-125=0 | | 6p-17=-33+2p | | 23=4-3n | | (3y-15)(y^2+4y-12)=0 | | 5-6x+9x=-15+5 | | 7+3r+9+6r= | | 9=-6(5)+b | | 25x^2+10x+4=0 | | g+7g= |